Theory of literary constellations. Giménez Caballero, analyst of the spanish intellectual field - Padró Nieto, Bernat (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
From 1925 to 1927 Ernesto Giménez Caballero combined writing reviews for El Sol with the creation of literary posters. One of them, entitled «Universe of contemporary Spanish literature», represents the Spanish intellectual field as the image of a constellated universe. This poster, which can be interpreted as a critical operation, constitutes a complete theory of literature from the late twenties of the last century, an alternative proposal to the customary historiographic periodization.
Keywords: Cultural magazines; Generation; Twenties; Intellectual Formations